Efecto de patologias dentales sobre la condicion corporal de los Equinos en la Hacienda Huasi-caballo. - Mera Macato, Bryan Javier (2022)
The present investigation was carried out with the objective to characterize dental effect on pathologies that influence body equine condition at Hacienda Huasi-Caballo Aloag Farm. For this purpose, 30 equines were studied; 17 females and 13 males, divided into ages ranging from 1 day to 5 years old on foal or filly section and from 5 years old onwards on mare and horse section. A data base was established with initial weight and initial body condition were calculated and with them oral examination was carried out, animals were sedated, and the examination was done in order of dental presentation, that is: incisors, canines, premolars and molars, identifying following pathologies: enamel tip 56%, dental hooks 7%, ramps 31%, periodontal diseases 6%. At statistical analysis in relation to dental pathologies with variables of feeding, age, and sex, a significant statistical relation was found (p<0.05) in enamel tips, dental hooks, ramps and periodontal diseases including age and sex, which represents that there is a relation between feeding and body condition with the pathology, Fisher exact test established (p>0.05) which represents that equines that suffered a low body condition, once pathologies were treated, these would improve. The correct treatment of dental pathologies in equines will contribute and favor their body condition, and therefore their welfare.